Does Postgraduate Education Deepen Temporomandibular Disorders Insights for Dental Professionals? - Zejin Liu; Jie Xiang; Yi Liu; Xueman Zhou; Yating Yi; Jun Wang; Xin Xiong (Pain Research and Management)
Conclusions: Postgraduate education deepened dental professionals’ understanding of TMDs. Students improved more in the domains of “diagnosis” and “treatment and prognosis,” whereas practicing dentists enhanced more in the “etiology” domain. To further advance postgraduate education, there is a need for more systematic course designs for TMDs, emphasizing the enhancement of knowledge related to examination methods and treatment options.